3506 PRMT5 is a novel therapeutic target to enhance radiation therapy for cancer treatment - Jake L Owens; Elena Beketova; Samantha Tinsley; Andrew Asberry; Xuehong Deng; Chang-Deng Hu (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: Prostate cancer is the second leading cause of cancer-related death among men in the U.S. and over half of all prostate cancer patients receive radiation therapy (RT). RT induces double-strand breaks (DSBs) in DNA which are lethal to cells if not repaired. While potentially curative, 10% of low-risk patients and 50% of high-risk patients treated with RT still experience tumor recurrence. Thus, identification of novel therapeutic targets to enhance RT will likely reduce prostate cancer mortality. The only clinical approach to enhance RT is androgen deprivation therapy, which targets androgen receptor (AR) signaling; however, its use is limited due to systemic side effects. We recently reported that PRMT5 epigenetically activates AR which led us to investigate if targeting PRMT5 sensitizes prostate cancer to RT. The goal of this project is to determine if PRMT5 is a therapeutic target for prostate cancer radiosensitization and analyze its mechanistic role in response to radiation. METHODS/STUDY POPULATION: To evaluate if targeting PRMT5 may sensitize prostate cancer cells to radiation, we performed a clonogenic assay of irradiated cells. To determine if PRMT5 is required for repair of radiation-induced DSBs, we performed foci analysis via immunocytochemistry. We then used RNA-seq, qPCR, western blot, and ChIP to evaluate a potential epigenetic role of PRMT5 in activating the expression of genes critical to DSB repair. To extend our findings, we analyzed clinical data from around 18,000 of cancer patients encompassing 43 cancer types to assess if PRMT5 expression correlates with the expression of its putative target genes. RESULTS/ANTICIPATED RESULTS: Targeting PRMT5 sensitizes prostate cancer cells to radiation independently of AR status. RNA-seq analysis revealed putative PRMT5 target genes including several involved in DSB repair and G2 arrest. Mechanistically, PRMT5 functions as a master epigenetic activator of DNA damage response (DDR) genes: PRMT5 maintains the basal expression of several DDR genes including BRCA1, BRCA2, and RAD51 and is recruited upon radiation to DDR gene promoters to activate their expression via histone methylation. Targeting PRMT5 decreases expression of these genes at the protein level and hinders repair of radiation-induced DSBs in multiple cancer and non-cancer cell types. Clinically, PRMT5 expression positively correlates with the expression of these DDR genes across all 43 cancer types analyzed. DISCUSSION/SIGNIFICANCE OF IMPACT: PRMT5 acts as a master epigenetic activator of genes involved in DDR and is critical for cells to survive radiation treatment. Importantly, PRMT5 epigenetically activates multiple genes that encode for well-characterized core repair proteins involved in HR (RAD51, RAD51AP1, RAD51D, BRCA1 and BRCA2) and NHEJ (NHEJ1, Ku80, XRCC4, and DNAPKcs), which may explain why PRMT5 is essential to repair IR-induced DSBs in several cell lines. As PRMT5 is overexpressed in many human cancers and its overexpression correlates with poor prognosis, our findings suggest that more efficient DSB repair via PRMT5 overexpression in these cancers may confer survival advantages particularly following DNA damaging treatments. Lastly, because targeting DSB repair is a clinically validated therapeutic approach for cancer treatment, our findings also suggest that PRMT5 targeting may be explored as a monotherapy or in combination therapy with radiation therapy or chemotherapy for cancer treatment.